2022
DOI: 10.1093/annweh/wxac062
|View full text |Cite
|
Sign up to set email alerts
|

Employment Precarity and Increased Risk of Hazardous Occupational Exposures Among Residents of High Socioeconomic Hardship Neighborhoods

Abstract: Background While there is evidence that workers in nonstandard employment arrangements are disproportionately exposed to recognized occupational hazards, existing studies have not comprehensively examined associations between employment precarity and exposure to occupational hazards for these workers in the USA. The aim of this study was to examine relationships between employment precarity and occupational hazards in two contiguous high socio-economic hardship neighborhoods in Chicago. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Community researchers, trained by academic co-investigators, conducted a crosssectional survey of 479 community residents from all parts of the neighborhood who self-identified as being precariously employed [24]. Of the 464 individuals who responded to the question about employment through temporary staffing companies in the prior 12 months, 190 (40.9%) reported that at least some of their paid hours came from temp agencies; 139 (30%) worked either most or all of their paid hours through temp staffing.…”
Section: Temporary Staffing Employment At the Intersection Of Race Et...mentioning
confidence: 99%
See 1 more Smart Citation
“…Community researchers, trained by academic co-investigators, conducted a crosssectional survey of 479 community residents from all parts of the neighborhood who self-identified as being precariously employed [24]. Of the 464 individuals who responded to the question about employment through temporary staffing companies in the prior 12 months, 190 (40.9%) reported that at least some of their paid hours came from temp agencies; 139 (30%) worked either most or all of their paid hours through temp staffing.…”
Section: Temporary Staffing Employment At the Intersection Of Race Et...mentioning
confidence: 99%
“…One staffing company had six amputations, four of the whole arm or whole hand and two of legs [11]. Precarious workers in the Greater Lawndale study, described in the section above, reported a high prevalence of exposure to chemical, physical, ergonomic, and traumatic injuries, though identifying those who were currently employed through temp staffing was impossible to distinguish [24].…”
Section: Work-related Injuries Among Temp Workersmentioning
confidence: 99%